Discovery and functional characterization of cysteine-rich peptides from medicinal plants - Loo, Shining (2018)
Natural product research has long been a fertile ground for drug discovery. An overwhelming majority of research effort has focused on small molecules, the primary and secondary metabolites with MW <1 kDa. With the advances in molecular biology, plant proteins with MW >10 kDa have also been extensively studied in life and agriculture sciences. However, peptides which occupy the chemical space between metabolites and proteins have been somewhat neglected. Most peptides are not considered as active components in herbal medicine as they are commonly perceived as being highly unstable. Typically, they are susceptible to degradation when subjected to high temperatures during herbal concoction preparation. Additionally, peptides generally denature and degrade in the harsh enzymatic and acidic environment of the gastrointestinal tract, resulting in no or very poor absorption and bioavailability. Disulfide-constrained cysteine-rich peptides (CRPs) with molecular weights of 2-6 kDa are hyperstable molecules and an underexplored frontier in drug discovery. They have the advantageous of both small molecules and proteins, and thus bridging both families in drug properties. Also these peptides have not considered as active compounds in medicinal plants. CRPs with their high cysteine residue contents possess multiple disulfide linkages to form highly constrained structures. The disulfide bridges forming strong covalent cross-linkages, imparts CRPs their hyper-stable characteristics. CRPs when compared to large proteins, are thus, less susceptible to degradation under heat, acid and proteolytic conditions. Moreover, desolvation of the tight disulfide core forces the side chains of amino acid residues to adopt an inside-out arrangement. This gives rise to the characteristically functionalized molecular surface of CRPs to be mostly amphipathic or hydrophobic. CRPs are classified into families based on their primary sequences, number of cysteines, cysteine pattern, disulfide connectivity and their three-dimensional structures. Well characterized families include plant defensins, hevein-like peptides and knottins. In terms of biological activities, CRPs display a myriad of biological functions such as antimicrobial, anti-insecticidal, immunomodulation as well as being ion channel blockers and enzyme inhibitors. In a mass spectrometry-driven discovery program for CRPs in medicinal plants, clusters of CRPs have been identified from three important families of medicinal plants. They are the Araliaceae family which include three ginseng species of Panax ginseng, Panax quinquefolius and Panax notoginseng, the Malvaceae family of Hibiscus sabdariffa, and the Cactaceae family of Pereskia bleo. My hypothesis is that CRPs present in these medicinal plants are an unexplored class of active constituents with potentials as putative oral biologics and leads for drug design and development. Here, my thesis describes the discovery and functional characterization of new CRPs in these three families and expands the chemical space of active constituents in medicinal plants. I used a combination of proteomic and transcriptomic methods to determine their sequences, NMR spectroscopy to determine their structures, and various biological assays to determine their functions. In all, I discovered 14 CRPs, designated as ginsentides, from Panax ginseng, Panax quinquefolius and Panax notoginseng, eight CRPs, designated as roseltides from Hibiscus sabdariffa, and one CRP, designated as bleotide pB1, from Pereskia bleo. The newly discovered CRPs with multiple disulfide linkages are highly constrained and holds promise as orally active biologics. To the best of my knowledge, my findings are novel as there is no reported work in the CRPs from these medicinal plants. My research topic could open new avenues in the field of natural product research.